The learning curve on uniportal video-assisted thoracoscopic lobectomy with the help of postoperative review of videos - Song, Zuodong; Yuan, Yu; Cheng, Chao; Luo, Qingquan; Cheng, Xinghua (Frontiers in Oncology, 2023)
Objectives: Video-assisted thoracoscopic lobectomy has become the preferred surgical approach in experienced centers, and uniportal approaches are becoming increasingly used. But the uniportal approach is still not widely applied presumably due to the learning difficulties of this complex procedure. The use of surgical videos may be helpful to accelerate the learning of this new techniques as in other fields. In this study, we aimed to analyze the learning curve of uniportal video-assisted thoracoscopic lobectomy with the help of postoperative review of videos. Methods: 114 patients with early-stage lung cancer who underwent uniportal video-assisted thoracoscopic lobectomy performed from 2020 to 2021 were reviewed in this study. We recorded the operation video for each patient and reviewed all the videos after surgery. The learning curves were assessed using cumulative sum analysis and the collected data of perioperative outcomes were assessed. Results: The CUMSUM curve showed its inflection points were around case 38 and 53. It was less compared with previous studies, which about 57–140 cases are needed to attain the proficient phase. The perioperative outcomes were similar in each phase, which included intraoperative blood loss (79.00 ± 26.70 vs 70.67 ± 26.64 vs 70.56 ± 27.23, p=0.0119), the length of hospital stay (3.60 ± 1.52 days vs. 3.23 ± 0.90 days vs. 3.06 ± 0.88 days, p=0.053), the rate of prolonged air leak and conversion to open thoracotomy. There was also no significant difference in the numbers and station of lymph node dissection among the three phases. Conclusions: Uniportal video-assisted thoracoscopic lobectomy is a safe and reliable approach. Recording and reviewing the operation video could help the surgeon to improve deficiencies and refine the procedure.